The Role of Family Education in the Development of Character According to Ki Hajar Dewantara - Afifah; Herman Nirwana; Dina Sukma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
For his achievements in politics and education, Ki Hajar Dewantara is also known as a figure who came up with important ideas in Indonesian national education. Through the concept of